2009
DOI: 10.1007/s00534-009-0195-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative exploration of biliary anatomy using fluorescence imaging of indocyanine green in experimental and clinical cholecystectomies

Abstract: Background/purpose We evaluated the usefulness of intraoperative exploration of the biliary anatomy using fluorescence imaging with indocyanine green (ICG) in experimental and clinical cholecystectomies. Methods The experimental study was done using two 40-kg pigs and the clinical study was done in 12 patients for whom cholecystectomy was planned from January 2009 to June 2009. Initially we used a laparoscopic approach for the evaluation of fluorescence imaging of the biliary system in the two pigs. Then the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 12 publications
2
45
0
3
Order By: Relevance
“…This is in concordance with preclinical data described by Matsui et al [30] and clinical studies of patients undergoing cholecystectomy [29,31]. A useful contrast between the common bile duct and surrounding tissue was observed ≄10 min after injection.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in concordance with preclinical data described by Matsui et al [30] and clinical studies of patients undergoing cholecystectomy [29,31]. A useful contrast between the common bile duct and surrounding tissue was observed ≄10 min after injection.…”
Section: Discussionsupporting
confidence: 80%
“…Because ICG is almost exclusively excreted into the bile, it can also be used for intraoperative NIR fluorescence exploration of the biliary anatomy [29,30,31]. This can be useful in patients with a difficult laparoscopic cholecystectomy, due to an aberrant biliary anatomy or an acute cholecystitis, for example.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36]38 For example, Schols et al 30 performed a feasibility study in a series of 15 laparoscopic cholecystectomies in which use of NIR-ICG facilitated significantly earlier identification and a clear delineation of both CBD and CD-in agreement with the results of our study. Using ICG, Ishizawa et al 32 reported identification of CD and CBD in a series of 52 patients undergoing laparoscopic cholecystectomy.…”
Section: Discussionsupporting
confidence: 91%
“…[27][28][29][30][31][32] The various moments at which ICG injection has been reported include 30-60 minutes before arrival in the operating room or the start of surgery, to just before induction of general anesthesia, and even following endotracheal intubation. [31][32][33][34][35][36] The dose used in the present study was 0.05 mg/kg. The first and third patients received ICG 1-2 hours prior to the start of surgery, based on the reported peak in concentration of ICG in bile 120 minutes after intravenous injection.…”
Section: Discussionmentioning
confidence: 99%
“…By real-time identification of the vital structures being the CD and CBD within the already adapted CVS technique, it may improve the outcome of LC. 16 27 28 NIRF imaging using ICG has been evaluated in various animal models [29][30][31] and in open, laparoscopic and single-incision laparoscopic cholecystectomies. 30 32-34 Promising results were presented for safe and successful intraoperative identification of the CBD and the CD, compared to conventional laparoscopic imaging.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%